Heterogeneity in Disordered Gambling: Decision-Making and Impulsivity in Gamblers Grouped by Preferred Form - Sharman, Steve; Clark, Luke; Roberts, Amanda; Michalczuk, Rosanna; Cocks, Rachel; Bowden-Jones, Henrietta (Frontiers in Psychiatry, 2019)
Background: Previous research has indicated that disordered gamblers display deficits in impulsivity and risky decision-making, compared to healthy control groups. However, disordered gamblers are not a homogenous group, and differences in performance on neurocognitive tasks may be related to the form of gambling in which an individual chooses to engage. The present study used neurocognitive tasks and questionnaire measures to ascertain group differences in gamblers grouped by preferred form of gambling. Method: Treatment-seeking pathological gamblers from the National Problem Gambling Clinic, London (n=101) completed a neurocognitive assessment comprising the Cambridge Gamble Task (CGT), the Stop Signal Task (SST), a Probabilistic Reversal Learning task (PRL) and the Kirby Monetary Choice Questionnaire, as well as questionnaire measures of gambling severity, impulsivity, depression and anxiety. Analyses compared gamblers who favored Fixed Odds Betting Terminals (FOBTs) (the modal form) to gamblers who preferred other forms of gambling (non-FOBT). Results: The FOBT group showed impaired decision-making under risk on the CGT compared to the non-FOBT group, choosing the likely option less on more uncertain decisions. The FOBT group made fewer perseverative errors on the PRL task, had lower depression and anxiety scores, and were less likely to have a family history of problem gambling than the non-FOBT group. Discussion: Decision-making and cognitive flexibility differences between gamblers grouped by gambling type supports preferred form as an important source of heterogeneity in Gambling Disorder. Decision making strategies and risk attitudes should be considered when approaching cognition-focused treatment strategies, allowing interventions to be targeted at specific cognitive deficits.